OFFSHORIZATION AS MAIN PROBLEM OF HOLDING GROUPS TAXATION - Y. Petlenko; A. Ivanov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
At this article, we have analyzed and systematized the conditions of holdings' activity to reduce the taxation level in countries and on the territory of special, so-called offshore, jurisdiction. In addition, we have made a suggestionhow to regulatean offshore capital flows inorder to prevent from tax frauds.